Dampak Pembangunan Infrastruktur Waduk Terhadap Penggunaan Lahan Kecamatan Ladongi (Studi Kasus: Waduk Ladongi) - Khaerul Alaudin; La Ode Hadini; Jamal Harimudin; Ahmad Hidayat (Universitas Halu Oleo, 2023)
In 2016 a reservoir was built in Ladongi District East Kolaka Regency which is targeted for completion in 2021. The existence of these reservoirs has an impact on existing land use. The purpose of this study is to analyze land use in 2013 and 2022 and identify changes in land use from 2013 to 2022. The materials used in the research are East Kolaka Regency SHP, 2021 BPS data, Landsat-8 OLI/TIRS imagery and RBI maps. The method used in this study uses the OBIA classification (object base image analysis) processed through ArcGIS 10.8. Based on the research results, land use changes in 2013 and 2022 are as follows: Forest has an area of10,592.60 acre reduced to 9,313.25 acre, open land area of 266.15 acre reduced to 209.70 acre, residential land area 360.84 acre increased to 1,019.53 acre, plantations of 2,461.30 acre experienced a decrease in area to 2,295.31 acre, the area of rice fields increased significantly from 2,059.66 acre to 2,725.44 acre, and water bodies whose initial area was 23.22 acre increased to 169.47 acre.